1973
DOI: 10.1042/cs0440397
|View full text |Cite
|
Sign up to set email alerts
|

Renal Control of Changes in the Compliance of the Interstitial Space: A Factor in the Aetiology of Renoprival Hypertension

Abstract: S U M M A R Y1. Measurements of plasma volume, haematocrit, extracellular fluid volume, blood pressure, venous pressure and interstitial tissue pressure were made in rats 4 days after unilateral nephrectomy. Measurements were repeated either 4 days after subsequent removal of the remaining kidney, or 4 days after anastomosis of the remaining ureter with the inferior vena cava. Extracellular fluid volume was expanded by giving 0.5% saline by mouth: in one series blood volume was expanded by injections of blood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
4

Year Published

1980
1980
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 11 publications
1
14
4
Order By: Relevance
“…29 '" Our values for IFP, which ranged from +0.3 to -2.8 mm Hg and averaged -1.5 mm Hg in all rats included in this study, were slightly higher (less negative) than that (-2.5 mm Hg) reported by others using the capsule technique in rats. 11 ' M However, measurements in the present study were made in conscious rats from capsules implanted subcutaneously in the dorsal shoulder area, whereas in the previous studies, measurements were made in anesthetized rats from capsules implanted subcutaneously in the groin" or thigh 11 areas. These differences in technique might be responsible for the small difference in the results between the present and the previous studies.…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…29 '" Our values for IFP, which ranged from +0.3 to -2.8 mm Hg and averaged -1.5 mm Hg in all rats included in this study, were slightly higher (less negative) than that (-2.5 mm Hg) reported by others using the capsule technique in rats. 11 ' M However, measurements in the present study were made in conscious rats from capsules implanted subcutaneously in the dorsal shoulder area, whereas in the previous studies, measurements were made in anesthetized rats from capsules implanted subcutaneously in the groin" or thigh 11 areas. These differences in technique might be responsible for the small difference in the results between the present and the previous studies.…”
contrasting
confidence: 39%
“…They suggested that increased tone of the capacitance vessels of the clipped rats was responsible for the fluid shift. Later, Lucas and Floyer 11 '" reported evidence of decreased interstitial compliance in experimental hypertension; and Floyer 1 ' suggested that a primary fall in the interstitial compliance could be the mechanism responsible for these and many Downloaded from http://ahajournals.org by on April 2, 2019 other of their observations. It was postulated that a combination of renal fluid retention and decreased interstitial compliance might together lead to hypertension despite a normal extracellular fluid volume."…”
mentioning
confidence: 99%
“…Following a long line of investigations Floyer et al concluded that an unidentified substance released from the kidney maintains normal tissue compliance in renal as well as extra renal tissues [17]. The present hypothesis proposes that this substance is EGF.…”
Section: Under Physiological Conditionsmentioning
confidence: 90%
“…18 In another study, subtotal nephrectomy resulted in hypertension, 19 the incidence of which was increased in rats given saline, but the level of hypertension was similar to those not given saline. 19 The studies of Lucas and Floyer 15 and Pelling and Ledingham 20 have shown that nephrectomized rats chronically receiving either 0.5% or 1% saline as drinking water become hypertensive over a period of several days. However, in the Pelling and Ledingham study, 20 allowing the rats to drink a large supplement of water rather than saline also increased blood pressure significantly to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…This rise in blood pressure following nephrectomy has been reported previously for rats and dogs;" l2 although this finding has not been observed consistently. l3 i4 Several explanations for increases in blood pressure following nephrectomy have been suggested, including reductions in tissue compliance 15 and lack of inactivation of an extrarenal pressor mechanism in the rat. 16 It is also possible that an increase in serum osmolarity accompanied by a concomitant elevation in the circulating ADH titer may contribute to postnephrectomy blood pressure elevation; however, these measurements have not been made.…”
Section: Discussionmentioning
confidence: 99%